Individualized 3D-printed bolus promotes precise postmastectomy radiotherapy in patients receiving breast reconstruction - Wang, Jun; Xiang, Zhong-zheng; Tan, Chen-feng; Zeng, Yuan-yuan; Yang, Tian; Wei, Xiao-yuan; Yu, Si-ting; Dai, Ze-lei; Xu, Ning-yue; Liu, Lei (Frontiers in Oncology, 2023)
Purpose To evaluate the efficacy and safety of 3D-printed tissue compensations in breast cancer patients receiving breast reconstruction and postmastectomy radiotherapy (PMRT). Methods and materials We enrolled patients with breast cancer receiving breast reconstruction and PMRT. The dose distribution of target and skin, conformability, and dose limit of organs at risk (OARs) were collected to evaluate the efficacy of the 3D-printed bolus. Radiation Therapy Oncology Group (RTOG) radiation injury classification was used to evaluated the skin toxicities. Results A total of 30 patients diagnosed between October 2019 to July 2021 were included for analysis. Among all the patients, the 3D-printed bolus could ensure the dose coverage of planning target volume (PTV) [homogeneity index (HI) 0.12 (range: 0.08-0.18)], and the mean doses of D99%, D98%, D95%, D50%, D2% and Dmean were 4606.29cGy, 4797.04cGy, 4943.32cGy, 5216.07cGy, 5236.10cGy, 5440.28cGy and 5462.10cGy, respectively. The bolus demonstrated an excellent conformability, and the mean air gaps between the bolus and the chest wall in five quadrants were 0.04cm, 0.18cm, 0.04cm, 0.04cm and 0.07cm, respectively. In addition, the bolus had acceptable dosage limit of OARs [ipsilateral lung: Dmean 1198.68 cGy, V5 46.10%, V20 21.66%, V30 16.31%); heart: Dmean 395.40 cGy, V30 1.02%, V40 0.22%; spinal cord planning risk volume (PRV): Dmax 1634 cGy] and skin toxicity (grade 1, 76.0%; grade 2, 21.0%; grade 3, 3.3%). Conclusion The 3D-printed bolus offers advantages in terms of dose uniformity and controllable skin toxicities in patients receiving breast reconstruction and PMRT. Further research is needed to comprehensively evaluate the effectiveness of the 3Dprinted bolus in this patient subset.